PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR SISTEM KOMPUTER SISWA KELAS X JURUSAN TEKNIK KOMPUTER JARINGAN DI SMK NEGERI 5 PADANG - Aprayanti Nasution; Nelda Azhar; Sukaya Sukaya (Universitas Negeri Padang, 2017)
The problem of the research is the low learning results of the students on the subjects of computer systems of SMK Negeri 5 Padang. This is due to several factors one of which is the method or strategy learning that is less innovative. The purpose of the research is to know the difference of result the study by using cooperative learning model of type Student Team Achievement Division (STAD) on the subjects of a computer system class X TKJ of SMK Negeri 5 Padang. This type of research is experimental. Where is to take the sampling by using random sampling technique. As the experimental class is class X TKJ A which will be treated by using cooperative learning model type STAD and control class is X TKJ B which will be treated by using inquiry model of learning. The technique of collecting data from post test, then analyzed for homogeneity test, normality test and hypothesis test. From the experimental class research results get the average value 82, 29, while the control class gets an average value of 76.93. The result of hypothesis calculation at significant level α = 0,05 got thitung> ttabel that is (2,182> 2,056) Because thitung is bigger than ttabel hence hypothesis (H0) rejected and hypothesis (Ha) accepted. From the calculation of the learning result Gain where O1 is the average of the experimental class and O2 is the control class, the percentage of learning result is increased by 6.79%. It can be concluded that by using cooperative learning model of Student Team Achievement Division (STAD) type has an effect on student learning result which proves from improvement of learning result. Keyword : Learning Resultss, Cooperative Learning Model TypeSTAD, Inquiry Learning Model.